Advances in the 5q- syndrome. - Boultwood, J; Pellagatti, A; McKenzie, A; Wainscoat, J (2010)
The 5q- syndrome is the most distinct of all the myelodysplastic syndromes with a clear genotype/phenotype relationship. The significant progress made during recent years has been based on the determination of the commonly deleted region and the demonstration of haploinsufficiency for the ribosomal gene RPS14. The functional screening of all the genes in the commonly deleted region determined that RPS14 haploinsufficiency is the probable cause of the erythroid defect in the 5q- syndrome. A mouse model of the human 5q- syndrome has now been created by chromosomal engineering involving a large-scale deletion of the Cd74-Nid67 interval (containing RPS14). A variety of lines of evidence support the model of ribosomal deficiency causing p53 activation and defective erythropoiesis, including most notably the crossing of the "5q- mice" with p53-deficient mice, thereby ameliorating the erythroid progenitor defect. Emerging evidence supports the notion that the p53 activation observed in the mouse model may also apply to the human 5q- syndrome. Other mouse modeling data suggest that haploinsufficiency of the microRNA genes miR-145 and miR-146a may contribute to the thrombocytosis seen in the 5q- syndrome. Lenalidomide has become an established therapy for the 5q- syndrome, although its precise mode of action remains uncertain.